Recycling of photovoltaic silicon waste for high-performance porous silicon/silver/carbon/graphite anode. (1st August 2021) - Wang, Lei; Xi, Fengshuo; Zhang, Zhao; Li, Shaoyuan; Chen, Xiuhua; Wan, Xiaohan; Ma, Wenhui; Deng, Rong; Chong, CheeMun
Highlights: Value-added utilization of photovoltaic silicon waste as anode for LIBs. Providing an idea for the commercial application of silicon/graphite anodes. Use of carbon from PVP pyrolysis as a linker between silicon and graphite. The pSi/Ag/C/G composite exhibits excellent electrochemical performance. Abstract: The rapid development photovoltaic industry has generated a huge amount of waste ultra-fine silicon cutting powder. The management and value-added recovery of silicon cutting waste is highly important for both environmental remediation and economic efficiency. In this work, silicon waste was used as a cost-effective raw material for the preparation of silicon/graphite anode for lithium-ion batteries. First, porous Si embedded with Ag particles (pSi/Ag) was produced by silver-assisted chemical etching (Ag-ACE). Then, pSi/Ag was loaded on a micron-sized graphite matrix (pSi/Ag/G), and organic carbon (C) produced by the pyrolysis of polyvinylpyrrolidone (PVP) acted as a link to closely connect pSi/Ag and graphite to form the pSi/Ag/C/G composite. The incorporated Ag particles and the porous structure improve electron transfer and mitigate the volume expansion effect of silicon. The novel design and structure of the anode can maintain the integrity of the electrode during cycling, and thus strongly improve cycling stability. The prepared pSi/Ag/C/G composite exhibited a large initial discharge capacity of 2353 mAh/g at 0.5 A/g and good initial coulombic efficiency of 83%, delivering a high capacity of 972 mAh/g at 1 A/g after 200 cycles. This work confirmed the possibility of the preparation of lithium battery silicon-carbon anode from silicon waste and provides a promising new avenue for value-added utilization of silicon cutting waste materials.